Trastorno de pánico a consecuencia del confinamiento por el covid-19 y su influencia en el entorno laboral de un joven de 25 años de la ciudad de Montalvo Provincia de Los Ríos - Castro Chichande, Madeleyn Dayana (2021)
This work was carried out in order to reduce the panic disorder of a 25-year-old young man as a result of the covid-19 pandemic and this in turn was influencing his work environment, for the solution of the conflict will be worked with the CBT psychotherapeutic approach, applying techniques such as focal cognitive therapy. Tests such as the Hamilton Scale and the Beck Anxiety Inventory were applied to verify the level of anxiety the patient was going through at that moment, in which a result was given on the Hamilton scale of 18-24 a moderate anxiety and in the Beck Anxiety Inventory 22-35 moderate anxiety, which means that the patient presents a moderate disturbance, which is interfering with their mood. For the cognitive-behavioral approach, the appearance of panic attacks is due to inappropriate reactions that people have in feelings of anguish or anxiety. Panic attacks are triggered as a result of a persistent cycle of mental perceptions. In this case we can say that an indication was given as a result of the multiple deaths worldwide due to the spread of the covid-19 virus. In this case study, the development of the variables is carried out and once developed, a search was made for the techniques to be used, and once the techniques were established, they were applied in order to obtain the diagnosis and proceed. to the treatment to get the results. The conclusion that in this case could be verified, that the catastrophic thoughts due to the covid-19 that caused the panic disorder if they were influencing his work environment since they were the ones that did not let him have the same potential and attitude that he had with users before the pandemic.